'The struggle isn't over': Shifting aid paradigms and redefining 'development' in eastern Myanmar. (March 2020) - Décobert, Anne
Highlights: Western donors have recently shifted to aid 'normalization' and from 'humanitarianism' towards 'development' in Myanmar. Members of Community-Based Health Organizations in the eastern borderlands perceive this shift as potentially harmful. These actors are continuing to struggle for the recognition of non-state health and governance systems. Aid economies designate different actors as legitimate, and territorialize border spaces differently, at different times. 'Development' is a site for struggles over recognition and inclusion in contested states. Local perspectives must be considered to ensure that international aid programs do not have unintended negative impacts. Abstract: In recent years, international optimism about Myanmar's fledgling democratization and peace process has contributed to a shift by many Western donors towards the 'normalization' of aid relations with the former pariah state, and from more 'humanitarian' to more 'development'-style approaches. Yet these shifts are not necessarily seen as progress by members of community-based health organizations, which operate under para-state governance systems in the borderlands. Instead, members of these organizations often describe the emerging 'development' paradigm in Myanmar as doing more harm than good. This article draws on long-term ethnographic research conducted over a decade-long period with ethnic minority health workers operating in Myanmar's eastern borderlands. It examines the meanings of 'humanitarianism' and 'development' – and of the 'humanitarian-development nexus' – from the perspective of local-level actors whose voices are still too often ignored in debates about international aid programs and their implementation. It finds that the reactions of the health workers to shifting aid paradigms and programs highlight what is at stake in an evolving politics of aid. These reactions are linked with a politics of suffering; with an ongoing struggle for recognition of non-state governance systems; and with impacts that international aid economies have in designating different socio-political actors as legitimate, and in territorializing border spaces in different ways, at different times. The health workers' attempts to advance an alternative model for 'development' in their communities in turn illustrate how different actors, who are brought together in an unequal 'aid encounter', are involved in an ongoing struggle over the legitimacy of competing systems of government and over the territorialization of border areas. Finally, the article contends that, without understanding local perspectives and engaging critically with the political implications of evolving aid interventions, international aid programs risk impacting negatively on conflict dynamics in contested and transitional states.